Particle accumulation and depletion in a microfluidic Marangoni flow - Orlishausen, Michael; Butzhammer, Lorenz; Schlotbohm, Daniel; Zapf, Daniel; Köhler, Werner (Soft Matter, 2017)
Thermosolutal and thermocapillary Marangoni convection at a liquid–gas interface in a microchannel structure of approximately 100 × 90 μm2 cross section creates a localized vortex that acts as a trap for micrometer and sub-micrometer sized tracer particles. Next to the vortex, depleted volumes appear that are entirely cleared of particles. This particle redistribution is caused by collisions of the tracers with the meniscus, which push the particles back onto the critical streamline with one particle radius distance to the meniscus. The streamlines between the meniscus and the critical streamline feed the depleted regions. Since the critical streamline depends on the particle radius, the effect leads to a particle fractionation according to their size. Diffusion allows only small particles to escape from the trap. Larger particles are permanently confined and their diffusion is rectified after every revolution at the meniscus, which produces a ratchet effect and increases the particle localization within the vortex.